Perceptions of a selected group of relatively affluent blacks regarding certain aspects of tourism - C. Boshoff; A. P. Du Plessis (South African Journal of Business Management, 1988)
Recent international and local developments have had a negative influence on the South African Tourism industry, particularly regarding the number of overseas tourists visiting the country. To compensate, the industry has renewed its interest in local options - particularly the potential and opportunities the black market offers. However, there appears to be a high degree of uncertainty about utilizing its potential. This study is an attempt to gain some insight into the tourism needs and requirements of a particular market segment, namely relatively affluent blacks. The findings reveal that affluent blacks do not exhibit tourism needs which are unique to that particular market segment, but do suggest definite needs and preferences. Information pertaining to these needs is essential for the marketer of tourism to ensure that appropriate marketing strategies are formulated which will allow for proper utilization of opportunities to the advantage of both marketer and consumer.
Keywords: 650